Efektivitas Penggunaan Aplikasi Kids Mode untuk Mengontrol penggunaan Smartphone selama Pembelajaran Daring - Siregar, Riski Ana Putri; Derta, Sarwo; Okra, Riri; Musril, Hari Antoni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
The use of smartphones in online learning is indeed very useful for students to learn. In fact, not all students use smartphones wisely to study, so students become unfocused in learning. The use of smartphones is misused in online learning such as for playing games, social media and others. The purpose of this study was to see how effective the kids mode application was to control the use of smartphones in online learning at SDN Sosa Timur District, Padang Lawas Regency, NorthSumatra. The type of research used is quantitative research. With a population of SDN Papaso IIand SDN Pir Trans Sosa 1A class VI with a total of 66 people. The sampling technique used ispurposive random sampling. While the test instrument used is a questionnaire with a Likert scale 4. The validity test of the questionnaire is valid with a value of rcount > rtable and a reliability test of 0.866> 0.70 which means reliable. The results of the study after being processed using SPSS obtained the hypothesis is 0.784 which means that H1 is accepted H0 is rejected, namely the use of the kids mode application to control the use of smartphones when online learning is effective and can be used in improving student learning outcomes, with an effectiveness of 61.5%. So, the use of the Kids Mode Application during the COVID-19 pandemic is effectively used as a tool used by parents in controlling students' learning when parents are busy, so that in this way parents no longer worry about their children when using smartphones.